Building a Greener Future: Exploring the Synergy of Sustainable Investments, Environmental Taxes, and Green Innovations in Emerging Economies - Afshan, Sahar; Tiwari, Sunil; Singh, Manjeet Kaur Harnek; Ho, Wai Kee (International Journal of Energy Economics and Policy, 2025)
The expansion of economic growth raises concerns about sustainable development in emerging countries, and in response, green growth has emerged as a critical policy option. Given the significance, the current study intends to explore the quantile-dependent association between green investment, green taxation, and green technologies with the green growth of emerging economies. The annual data from 2000 to 2023 has been collected to accomplish the desired goal of the study. The advanced Method of Moments Quantile regression (MMQR) was employed after examining the cross-sectional dependencies, stationarity properties, and presence of cointegration among the variables. The outcomes indicated that lower levels of green growth are not influenced by implementing environmental taxations in emerging economies. Furthermore, the empirical findings assert that encouraging investments in renewable energy and green technologies complement low, medium and high level of green growth in emerging countries. The study suggests that green policies encourage the adoption of green finance systems to embrace modern technologies in the manufacturing process in order to achieve sustainable development thereby anticipating several regional policy implications to accelerate green growth.